TEACHER DIFFICULTIES IN TEACHING LINGUISTICS: A SEMANTIC MASTERING - Saragih, Ibnu Ziat; Daulay, Sholihatul Hamidah; Dalimunte, Muhammad (Universitas PGRI Sumatera Barat, 2024)
Teaching semantic concepts in tertiary linguistics programs has presented significant challenges for instructors. However, there needs to be a more in-depth exploration of this issue, hindering the understanding of underlying problems that impede effective semantics instruction. This qualitative phenomenological study aims to fill this gap by examining the difficulties faced by 15 experienced linguistics lecturers while teaching semantics courses to undergraduate and postgraduate students. Through in-depth semi-structured interviews, four major themes emerge, encompassing key pedagogical obstacles. First, students needed help to grasp complex, abstract, and philosophical semantic theories. Secondly, the technical precision required for semantic role labelling and predicate logic translation proved overwhelming for learners. Thirdly, establishing relevance to real-world applications proved to be challenging. Finally, excessive abstractions led to widespread student disengagement, motivation issues, and avoidance. The findings highlight the significant need for instructional design and pedagogical support in tertiary linguistics education to improve semantic teaching ability and learning outcomes. Proposed measures include specialized instructor training, scaffolding complex concepts, leveraging technology, fostering interdisciplinary connections, and enhancing social perceptions of semantics utility. These initiatives aim to develop the sophisticated semantic thinking required for advanced linguistics practice. Further quantitative research is suggested to validate and generalize these qualitative insights, informing nationwide improvements in systemic semantics curriculum.